Evaluation of Displacements Caused by Strike-Slip Deformations Using Correlation Characteristics Based on Potential Field Data - Senchina Natalia; Asoskov Artem; Gorelik Gleb (Russian Journal of Earth Sciences)
The identification of faults is a common objective in geophysical potential field methods. Vertical discontinuities such as reverse faults, also known as tectonic faults, can easily be distinguished through their effect on gravity and magnetic fields, appearing as gradient zones or areas of change in the field. However, identifying strike-slip faults is one of the biggest challenges for potential field methods as they are characterized by a complex series of anomalies with varying signs in the fault zone, as well as displacement of anomaly axes between the strike-slipped blocks. The goal of this study is to suggest a transformation that would aid in the identification of shear zones through the calculation of the displacement along the discontinuity. The proposed approach involves calculating the correlation coefficient between parallel profiles using moving windows. The position of the window with the highest calculated correlation coefficient allows estimating of the discontinuity displacement magnitude. The method was tested using a synthetic field and data from the magnetic field of the Kolbeinsi Ridge.